Medication adherence and blood pressure control amongst adults with primary hypertension attending a tertiary hospital primary care clinic in Eastern Nigeria - Gabriel U.P. Iloh; John N. Ofoedu; Patrick U. Njoku; Agwu N. Amadi; Ezinne U. Godswill-Uko (AOSIS, 2013)
Background: As the case detection rates of hypertension increase in adult Nigerians, achieving target blood pressure (BP) control has become an important management challenge. Objectives: To describe medication adherence and BP control amongst adult Nigerians with primary hypertension attending a primary care clinic of a tertiary hospital in a resource-poor environment in Eastern Nigeria. Methods: A cross-sectional study was carried out in 140 adult patients with primary hypertension who have been on treatment for at least 6 months at the primary care clinic of Federal Medical Centre, Umuahia. A patient was said to have achieved goal BP control if the BP was < 140 per 90 mmHg. Adherence was assessed in the previous 30 days using a pretested researcher-administered questionnaire on 30 days of self-reported therapy. Adherence was graded using an ordinal scoring system of 0-4; an adherent patient was one who scored 4 points in the previous 30 days. Reasons for non-adherence were documented. Results: Adherence to medication and BP control rates were 42.9% and 35.0% respectively. BP control was significantly associated with medication adherence (p = 0.03), antihypertensive medication duration ≥3 years (p = 0.042), and taking ≥ one form of antihypertensive medication (p = 0.04). BP at the recruitment visit was significantly higher than at the end of the study (p = 0.036). The most common reason for non-adherence was forgetfulness (p = 0.046). Conclusion: The rate of BP control amongst the study population was low, which may be connected with low medication adherence. This study urges consideration of factors relating to adherence alongside other factors driving goal BP control.